2013
DOI: 10.1002/cncr.28216
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of multiparametric magnetic resonance imaging in confirming eligibility for active surveillance for men with prostate cancer

Abstract: BACKGROUND: Active surveillance (AS) is an attempt to avoid overtreatment of clinically insignificant prostate cancer (PCa); however, patient selection remains controversial. Multiparametric prostate magnetic resonance imaging (MP-MRI) may help better select AS candidates. METHODS: We reviewed a cohort of men who underwent MP-MRI with MRI=Ultrasound fusion-guided prostate biopsy and selected potential AS patients at entry using Johns Hopkins criteria. MP-MRI findings were assessed, including number of lesions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(156 citation statements)
references
References 31 publications
6
148
1
1
Order By: Relevance
“…Given the large number of recent studies that have demonstrated the utility of targeted biopsy for intraprostatic lesions, this technique is likely to become increasingly widespread. 8,10,[22][23][24] The present study supports targeted biopsy of the SVs when indicated by imaging. It should be noted that the targeted biopsies performed in this study were based on diagnostic MRIs obtained on a 3-Tesla magnet with an endorectal coil and MP-MRI sequences, including T2-weighted, DCE, DWI, and MRS.…”
Section: Discussionsupporting
confidence: 75%
“…Given the large number of recent studies that have demonstrated the utility of targeted biopsy for intraprostatic lesions, this technique is likely to become increasingly widespread. 8,10,[22][23][24] The present study supports targeted biopsy of the SVs when indicated by imaging. It should be noted that the targeted biopsies performed in this study were based on diagnostic MRIs obtained on a 3-Tesla magnet with an endorectal coil and MP-MRI sequences, including T2-weighted, DCE, DWI, and MRS.…”
Section: Discussionsupporting
confidence: 75%
“…The literature search identified 30 original articles that were included for review: 14 on magnetic resonance imaging (MRI) [8][9][10][11][12][13][14][15][16][17][18][19][20][21], 5 on serum markers [22][23][24][25][26], 5 on urinary markers [27][28][29][30][31], 4 on histopathology markers [32][33][34][35], and 2 on germline genetic markers [36,37]. Figure 1 presents the search strategy and study selection flowchart.…”
Section: Search Resultsmentioning
confidence: 99%
“…Stamatakis et al reported the findings of 3-T MP-MRI in AS patients according to the Johns Hopkins criteria (n = 85) [15]. The number of lesions on MRI, rate of suspicion of lesions (number of positive sequences), and lesion density (lesion volume divided by prostate volume) were associated with findings at confirmatory biopsy, including MRItransrectal ultrasound (TRUS) fusion-guided biopsies.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…61 The National Cancer Institute nomogram, which uses only mpMRI criteria, generated an AUC of 0.71 for predicting candidates for AS in a cohort of 85 patients, 60 of whom had very low-risk disease (≤cT1c, PSA density <0.15, biopsy Gleason score ≤6, ≤ 2 positive biopsy cores, and ≤50% cancer involvement in any biopsy core). 62 This nomogram was developed with biopsy pathology as an endpoint, which is a method that has not been validated. Thus, while mpMRI appears to provide some incremental value in selecting candidates for AS, it is far from perfect and remains limited by an inability to consistently detect clinically significant lesions, with reported false-negative rates of up to 16%.…”
Section: Multiparametric Mri In Active Surveillancementioning
confidence: 99%
“…Performing mpMRI prior to entering AS can reduce the number of inappropriate AS candidates by 29% (Figures 1 and 2). 62 Once a patient has initiated AS, mpMRI can be useful in demonstrating lesion stability (Figure 3) but currently lacks the sensitivity to reliably detect higher-risk lesions during follow-up. As such, continued serial biopsies are recommended until mature data indicate that a stable mpMRI may in fact preclude subsequent biopsy.…”
Section: Multiparametric Mri In Active Surveillancementioning
confidence: 99%